Web based indexing and retrieval system using SQL server. - Chong, Damon Chew Wai. (2008)
This paper studies the concerns related to Web-based indexing and retrieval systems that used SQL servers. A prototype was created to examine some of the common performance issues and challenges faced by typical Web index, search and retrieval applications.